OP0087 The Association of Extra-Articular Manifestations with Disease Duration in Axial Spa: Results from The (Be-) Giant Cohort and The Aspect Study. (15th July 2016) - Varkas, G.; Cypers, H.; Vastesaeger, N.; Van Praet, L.; Carron, P.; Van den Bosch, F.; Elewaut, D.; ,
Abstract : Background: The prevalence of extra-articular manifestations (EAMs) in ankylosing spondylitis (AS) is well-known. However, as the diagnosis of axial spondyloarthritis (AxSpA) is now made much earlier in the disease the prevalence of the EAMs may be different. Moreover, the introduction of anti-TNF therapy may have altered the incidence of EAMs. Objectives: to assess the association of EAMs with disease duration in AxSpA patients (n=215) in the post-anti-TNF era compared to a historic cohort of Belgian AS patients (n=847) from the pre-anti-TNF era. Methods: The BelGian Inflammatory Arthritis and spoNdylitis cohorT (Be-Giant) and The Ghent Inflammatory Arthritis and spoNdylitis cohorT (GIANT) are post-anti-TNF observational cohorts that include consecutive patients since 2010, diagnosed with AxSpA by their treating rheumatologist. Patients who fulfill the ASAS classification criteria, are prospectively followed every 6 months. Follow-up consisted of patient-reported outcomes, a standardized clinical examination (peripheral joints, entheses, axial metrology), standard laboratory analysis and imaging. The ASPECT cohort is a Belgian pre-anti-TNF cross-sectional AS database containing information on 847 patients who fulfilled the New York modified criteria for AS between February 2004 and February 2005. Results: In the (Be-)Giant cohort and ASPECT cohort respectively 47% and 67.9% of patients were male. Mean age was 34.5 (SD 9.6) in the (Be-)Giant cohort and 44.6 (SD 12.1) in the ASPECT cohort. Mean symptom duration was respectively 7.9 and 18.5 years. HLA-B27 was positive in respectively 76.5% and 83% of patients with HLAB27 determination. In a cross-sectional analysis of the baseline data of 215 AxSpA patients from the (Be-) GIANT cohorts, about 66.5% (143/215) of patients had not experienced any EAMs compared to only 58% (491/847) of AS patients in the ASPECT cohort. Additionally, 71.5% (112/144) of patients with a symptom duration of less than 10 years had not experienced any EAMs at baseline in the (Be-)GIANT cohort. However, in patients with more than 10 years of symptom duration, only about half of patients remained EAM- free (P=0.021). Similarly, in patients from the ASPECT cohort with a disease duration of less than 10 years, 70% of patients (304/434) had not experienced any EAM at baseline, whereas only 39% (79/203) of patients remained EAM- free after 20 years of disease. A subanalysis of 118 newly diagnosed non-radiographic AxSpA (nr -AxSpA) patients demonstrated a prevalence of 70.3% (83/118) of EAM-free patients at diagnosis. Conclusions: The prevalence of extra-articular manifestations seems to increase with disease duration both in the pre-anti-TNF and the post-anti-TNF era, and may be linked to longer cumulative exposure to inflammation. Disclosure of Interest: None declared